Social Media Literacy of Tourism Village Activists in Wanurejo, Borobudur: Does Age Matter? - Sari, Yoana Puspita; Pambuko, Zulfikar Bagus; Muliawanti, Lintang; Fidian, Athia (Universitas Ahmad Dahlan, 2022)
Borobudur Temple is one of the five Indonesian super-priority destinations targeted to be the